A Minimally Nonanthropocentric Economics: What Is It, Is It Necessary, and Can It Avert the Biodiversity Crisis?. (5th May 2021) - Vucetich, John A; Damania, Richard; Cushman, Sam A; Macdonald, Ewan A; Burnham, Dawn; Offer-Westort, Thomas; Bruskotter, Jeremy T; Feltz, Adam; Eeden, Lily Van; Macdonald, David W
Abstract: An important line of scholarship concludes that stemming the biodiversity crisis requires widespread nonanthropocentric modes of action and decision-making. In this regard, knowing what would even constitute a nonanthropocentric economic decision-making framework is hobbled by failing to recognize a conflation in the taxonomy of capital as supposed by traditional (anthropocentric) economics. We explain how natural capital (a basic category in anthropocentric economies) conflates natural capital without intrinsic value and natural capital with intrinsic value. Recognizing this conflation allowed us to identify instances of quantitative analyses that have elements of nonanthropocentrism but that seem not to have been previously recognized as such. We also explore inescapable consequences of recognizing this conflation, including the need to better understand how economic decision-making should take account for interspecies distributive justice and human well-being. That second need augments independent calls by economists and policy experts to take better account of human well-being.